The influence of hardware imperfections onto wave-field synthesis accuracy - Lorenz, Mario; Schirmer, Christopher; Damm, Robert; Kotterman, Wim A.Th; Del Galdo, Giovanni; Heuberger, Albert; Landmann, Markus H. (Proceedings of 19th International ITG Workshop on Smart Antennas, WSA 2015, 2015)
For functional testing of prototypes for mobile communications, global navigation satellite systems, or cognitive radio we propose an over-the-air testbed using wave-field synthesis. When going from simulations to practical implementations, several imperfections of practical devices need to be considered. The effects induced by these imperfections influence the accuracy of the synthesized wave field. Typical causes are temperature variations, mechanical vibrations, or noise. This contribution analyzes the influence of imperfections of the components, like signal generators that feed the OTA antennas, contributing to synthesis errors of the wave field in a simulative manner.
CRIS-Team Scopus Importer:2025-11-10